A Systematic Review and Meta-Analysis on the Accuracy of Fluorodeoxyglucose Positron Emission Tomography/ Computerized Tomography for Diagnosing Periprosthetic Joint Infections - Hu, Mei; Chen, Guangwen; Luo, Lin; Shang, Lan (Frontiers in Surgery, 2022)
Objective: Positron emission tomography/computerized tomography (PET/CT) has become popular for diagnosing periprosthetic joint infections (PJI). However, the diagnostic accuracy for this technique has varied from report to report. This meta-analysis was performed to assess the accuracy of PET/CT for PJI diagnosis. Material and methods: We conducted a systematic search of online academic databases for all studies reporting the diagnostic accuracy of PET/CT for PJI. Meta-analysis was performed using STATA software. Results: 23 studies, containing data on 1,437 patients, met inclusion criteria. Pooled sensitivity and specificity of PET/CT for diagnosing PJI were 85% (95% CI: 76%, 91%) and 86% (95% CI: 78%, 91%), respectively with an AUC of 0.92. LRP was 6.1 (95% CI: 3.8, 9.7) and LRN was 0.17 (0.11, 0.28), indicating that PET/CT cannot be used for confirmation or exclusion of PJI. There was significant inter-study heterogeneity, but no significant publication bias was noted. Conclusions: Our study found that PET/CT has an important role as a diagnostic tool for PJI with high sensitivity and specificity. Further studies exploring its accuracy in different PJI locations remain necessary.